Means of Creating the Media Image of a Candidate to the Post of Mayor through Contextual Argumentation (on the materials of the texts about the 2018–2019 elections in Moscow, Vilnius and Belgrade) - Makarova, Viktorija; Shulus, Aleksey (Respectus Philologicus, 2020)
In political cultures of a number of countries, the creation of a politician’s media image is based on the fundamental principle of his/her work being formulated as the achievement of the goal of ensuring a nation’s well-being and a country’s development. The present article demonstrates concrete similarities and differences discernible in the construction of a politician’s media image in the Russian, Lithuanian and Serbian media discourses from a rhetorical perspective. The methodological basis of the investigation is provided by the ideas of the new rhetoric and Ch. Perelman and L. Olbrechts-Tyteca’s assumption concerning the fact that the speaker’s ideas are accepted (or not accepted) by the audience not depending on the degree of the strictness of logical propositions and conclusions, but rather on the fact of whether the hearers have adhered to the grounds given by the speaker. Consequently, a researcher analysing the ways text influences the consciousness of those receiving it may identify shared truths and value judgements. On the basis of the analysis of contextual argumentation used for the creation of the media image of the candidates for the post of mayor in the three media discourses, an attempt to establish shared truths and values as well as certain regularities in the process of media image creation characteristic of the Russian, Lithuanian and Serbian media discourses has been made.